2019
DOI: 10.22555/ijelcs.v4i2.2835
|View full text |Cite
|
Sign up to set email alerts
|

Learning Organizational Practices and Job Satisfaction: A Case of IT Sector of Karachi

Abstract: With the increase of globalization and technological advancements since the last few decades, organizations have gone through several changes in terms of workplace diversity, learning differentiation as well as organizational culture.This study aims to test the relationship between Learning Organization and Job Satisfaction in the IT Sector of Karachi. Data were collected from 209 such employees of the IT sector who have been working for the same organization for at least one year. Multiple Regression Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Studies on the importance of ATC, its predictors and outcomes are available with many meaningful remarks (Pincus et al, 2017;Mula et al, 2017). The predictors tested in the present study are grounded in the learning organization concept, yet not new but feasible at all times (Ghayas & Khan, 2019;Pedler & Burgoyne, 2017;Vince, 2018). Suifan & Allouzi (2018) showed that the learning culture enables organizational performance, and commitment to the organization plays a mediating role.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Studies on the importance of ATC, its predictors and outcomes are available with many meaningful remarks (Pincus et al, 2017;Mula et al, 2017). The predictors tested in the present study are grounded in the learning organization concept, yet not new but feasible at all times (Ghayas & Khan, 2019;Pedler & Burgoyne, 2017;Vince, 2018). Suifan & Allouzi (2018) showed that the learning culture enables organizational performance, and commitment to the organization plays a mediating role.…”
Section: Literature Reviewmentioning
confidence: 86%
“…In this direction, organizations should give importance to human resources (Malik & Garg, 2020). It is stated that the most important power of learning organizations is employees, who are human resources, and the empowerment of employees contributes significantly to the formation of a learning organization (Ghayas & Khan, 2019). It is revealed that human resources leaders take an important role in the process of making an organization that learns the organization by undertaking an integrative task in the organization.…”
Section: Human Resources In Tourism Industrymentioning
confidence: 99%
“…Therefore, the companies are looking for anything that may help them gain the competitive edge. The use of technology is one such element that may help the businesses in gaining the competitive edge [2]. Hence, the importance of using modern ERP Systems etc.…”
Section: Introductionmentioning
confidence: 99%